(untitled) (The Research of Medical Science Review, 2025)
A series of aryl azo dyes was synthesized through a solvent-free mechanochemical grinding approach, offering an environmentally friendly alternative to conventional synthetic methods. The process involved diazotization of aniline derivatives, followed by coupling with phenolic compounds under grinding conditions, yielding dyes with high purity and intense coloration. The reaction progress was monitored using thin-layer chromatography (TLC), and structural confirmation of the final products was carried out using FTIR and NMR Spectroscopy. The dyes displayed notable thermal stability and potential applications in textiles, sensors, and biomedicine. In addition to structural analysis, biological activity was evaluated using biofilm inhibition and hemolysis assays. Eight compounds (RS-01 to RS-08) were tested against Bacillus subtilis (B. subtilis) and Escherichia coli (E. coli). RS-08 exhibited the highest biofilm inhibition in B. subtilis at 76.11%, whereas RS-05 showed a slight promotion of biofilm at -1.13%. In E. coli, RS-05 and RS-06 demonstrated moderate inhibition (54.35% and 49.74 %, respectively), whereas RS-07 and RS-08 promoted biofilm formation, as indicated by the negative inhibition values. The hemolytic activity was assessed using human blood cells. RS-05 caused the highest hemolysis (56.2%), whereas RS-08 exhibited the lowest hemolysis (18.51%), indicating lower cytotoxicity. These findings support the potential of the selected azo dyes for biocompatible applications, with RS-08 emerging as a promising candidate owing to its potent biofilm inhibition and minimal hemolytic impact.